Dietary habits during the 2 months following the Chernobyl accident and differentiated thyroid cancer risk in a population-based case–control study. (February 2018) - Xhaard, Constance; Rubino, Carole; Souchard, Vincent; Maillard, Stéphane; Ren, Yan; Borson-Chazot, Françoise; Sassolas, Geneviève; Schvartz, Claire; Colonna, Marc; Lacour, Brigitte; Woronoff, Anne Sophie; Velten, Michel; et al.
Highlights: We studied the impact of contaminated food ingestion after the Chernobyl accident in a case-control study on differentiated thyroid cancer risk. Food items were fresh milk, dairy products and leafy vegetable, the most contaminated food after the Chernobyl accident. No significant association between fresh dairy products or milk and differentiated thyroid cancer risk has been evidenced. However we find a slightly increased risk associated with leafy vegetable consumption. The present analysis lacks power for less contaminated areas. Abstract: Background: The Chernobyl nuclear power plant accident occurred in Ukraine on April 26th 1986. In France, the radioactive fallout and thyroid radiation doses were much lower than in highly contaminated areas. However, a number of risk projections have suggested that a small excess in differentiated thyroid cancer (DTC) might occur in eastern France due to this low-level fallout. In order to investigate this potential impact, a case–control study on DTC risk factors was started in 2005, focusing on cases who were less than 15 years old at the time of the Chernobyl accident. Here, we aim to evaluate the relationship between some specific reports of potentially contaminated food between April and June 1986 – in particular fresh dairy products and leafy vegetables – and DTC risk. Methods: After excluding subjects who were not born before the Chernobyl accident, the study included 747 cases of DTC matched with 815 controls. Odds ratios were calculated using conditional logistic regression models and were reported for all participants, for women only, for papillary cancer only, and excluding microcarcinomas. Results: The DTC risk was slightly higher for participants who had consumed locally produced leafy vegetables. However, this association was not stronger in the more contaminated areas than in the others. Conversely, the reported consumption of fresh dairy products was not statistically associated with DTC risk. Conclusion: Because the increase in DTC risk associated with a higher consumption of locally produced vegetables was not more important in the most contaminated areas, our study lacked power to provide evidence for a strong association between consumption of potentially contaminated food and DTC risk.